Interactions of plant food bioactives‐loaded nano delivery systems at the nano‐bio interface and its pharmacokinetics: An overview. Issue 2 (20th January 2022) - Shanmugam, Haripriya; Rengarajan, Chitra; Nataraj, Swathika; Sharma, Aashima
Abstract: Plant food bioactives (PFBs) offer immense health benefits with a greater scope for treating various life‐threatening diseases and lifestyle disorders. Knowing their therapeutic potentials, a lot of research works are being carried out on formulating PFBs‐loaded nano delivery systems (NDSs) to enhance their bioefficacy. However, limited information are available on the interactions occurring at the nano‐bio interface. Therefore, studies on nano‐bio interactions are of immense importance towards designing/formulating effective NDSs for PFBs. Understanding the significance of nano‐bio interface of food bioactive‐loaded NDSs would help us to predict the formation of biocorona as well as the correlation between the nanoparticles and their surrounding environments that are influenced by the NDS's physicochemical properties. The physicochemical characteristics of NDSs like size, shape, and surface charge will decide their fate in the biological fluids and have been discussed in detail. As the bioactives‐loaded NDS enters the gastrointestinal tract, formation of biocorona including protein and enzyme corona at the nano‐bio interface will takes place. Subsequently, the fate of PFBs‐loaded NDSs influences the absorption, distribution, metabolism, and excretion (ADME) processes and thereby its bioavailability, bioefficacy, and biosafety. The current review focuses on understanding the journey of PBFs‐loaded NDSs, the nature of interactions happening at nano‐bio interface, and its pharmacokinetics properties. In addition, a specific case study approach on curcumin‐loaded NDSs, and its reported interactions at nano‐bio interface, including ADME mechanism are comprehensively presented. Abstract : Plant food bioactives loaded nano delivery systems representing major interacting components at nano‐bio interface and its pharmacokinetics